Digital twins for the sustainable maintenance of ageing waterway infrastructure - B. Jost; K. Holste; C. Hesse (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
A substantial part of the ageing waterway infrastructure in Europe, including locks, quay walls, and coastal protection structures, is approaching the end of its service life, necessitating either replacement or extensive repairs to prevent hazards. The integration of digital twins offers transformative opportunities for the complete digitalization of these assets, enhancing structural inspections and maintenance processes. This paper explores methods and solutions developed through the 3D HydroMapper, port_AI, and Port:Evolution research projects funded by the Federal Ministry for Digital and Transport, Germany from 2018 to 2027. By utilizing mobile platforms for geodata collection, both above and below water, and employing technologies such as sonar, photogrammetry, and laser scanning, comprehensive and precise surface scans and images of infrastructure can be achieved. These scans enable early detection of damage, facilitating timely repair measures and extending the service life of structures. The fusion of diverse georeferenced data types within a cloud portal ensures efficient sharing and lifecycle management, contributing to sustainable infrastructure maintenance. This paper provides a full workflow from the acquisition of waterway infrastructure below and above water to the planning of its maintenance.